Functional expression of Arabidopsis thaliana anthranilate synthase subunit I in Escherichia coli. - Bernasconi, P (1994)
Anthranilate synthase is involved in tryptophan (Trp) biosynthesis. Functional expression of subunit I from Arabidopsis (ASA1) was achieved in bacteria as a protein fused with glutathione S-transferase (GST). The active product was purified in a single step on a glutathione-Sepharose column. The Vmax (45 nmol min-1mg-1), the apparent K(M) for chorismate (180 microM), and the feedback inhibition by Trp (complete inhibition by 10 microM Trp) of the purified fusion product (GST-ASA1) were comparable to anthranilate synthase purified from plants. Polyclonal antibodies raised against the fusion project and purified by affinity chromatography on a GST-ASA1-Sepharose column cross-reacted with a 61.5-kD protein in a partially purified anthranilate synthase preparation from corn seedlings. GST-ASA1 cleavage by thrombin, as well as site-directed mutagenesis modifications of the Trp allosteric site, inactivated the recombinant protein.